Outer Code Mixing in Whatsapp Banten Sinergi Group (Sociolinguistic Study) - Dwi Septiani (Prodi Sastra Indonesia Universitas Pamulang, 2022)
This study aims to describe outer code mixing as a medium for interacting between teenagers in the WhatsApp group and the factors behind the outward code mixing. In this study, a qualitative descriptive method was used. The data in this survey is in the form of a description, namely a dialogue between members within the Banten Sinergi WhatsApp Group in which there is mixed code outside. There were 29 data taken in the Banten Sinergi WhatsApp Group in May 2019—July 2019. The results of this study were that there were 20 speech data containing words or clauses in English and 6 speech data containing words in Arabic. The background factor for the occurrence of outer code mixing in the Banten Sinergi WhatsApp Group is the linguistic factor and the attitude of the speakers.